"Frontier" Regions: Territorial Identity and the Perception of "Specialness". Issue 3 (2nd November 2018) - Zadorin, Igor V.
ABSTRACT: This article presents the results of a comprehensive study conducted by the ZIRCON Research Group in four frontier regions of Russia (Crimea, Primorsky Krai, and Kaliningrad and Murmansk oblasts) and two non-frontier control regions (Kostroma Oblast and Chuvashia). 1 The research methods included collection of data on the current situation in the regions and a series of focus group discussions that included representatives of small and medium-sized businesses, civil society, and the expert community. The sample included 5, 000 adults (over the age of 18) in these regions. The study focused on the following components: the rootedness of the population (whether people are potentially ready to move to another region); territorial identity; perception of the region of residence and its population; perception of the characteristics of the inhabitants of the region; the level of trust and the propensity for solidarity; the level of openness; the presence/absence of a "defense consciousness"; views on prospects for the development of the region and its "mission"; the perception of the region as "special" in comparison to other regions of the Russian Federation; the level of political loyalty of the population; the perception of and attitude toward the "federal center"; the attitude toward the expansion of the powers of the region. The study's ultimate goal was to identify the link between the territorial identity of the population of the participating regions and their peoples' perceptions of the prospects for the development of the region, including its relations with the federal center and other constituent entities of the Russian Federation.